2015
DOI: 10.15740/has/ijas/11.1/77-80
|View full text |Cite
|
Sign up to set email alerts
|

Response of wheat varieties to different levels of fertilizer on growth and yield under late sown condition

Abstract: A field experiment was conducted at Department of Agronomy, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani during Rabi season of 2009-10 with a view to find out a response of different fertilizer levels and varieties on growth and yield of wheat and to find interaction effect of fertilizer levels and varieties. The results of study showed that the fertilizer level 120:60:60 kg NPK ha-1 was found beneficial in improving growth characters, yield attributes and yield as compared to 80:40:40 kg NPK ha-1 , 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The findings of Sarwer et al [12], who claimed that the application of organic manures in conjunction with mineral fertilizers increased plant development, are consistent with these results. Findings on growth characteristics of wheat reported by Kale et al [13] support the results obtained in this study.…”
Section: Growth Attributessupporting
confidence: 92%
“…The findings of Sarwer et al [12], who claimed that the application of organic manures in conjunction with mineral fertilizers increased plant development, are consistent with these results. Findings on growth characteristics of wheat reported by Kale et al [13] support the results obtained in this study.…”
Section: Growth Attributessupporting
confidence: 92%
“…The availability of sufficient nutrients may have contributed to the enhanced vegetative development of plants, which in turn led to the higher dry matter at higher fertility levels. Both Laghari et al [17]; Kale et al [18] reported results that were similar. Pandey et al [19] reported that the consisted of three sulphur levels Singh et al [20] reported that the irrigation levels has significant effects on wheat growth and characteristics, as well as grain and straw yields.…”
Section: Response Of Moisture Regimes and Nitrogen Sources On Growth ...mentioning
confidence: 63%
“…Nitrogen is reported to play a role in protein formation as a component of chlorophyll; thus, an adequate supply of nitrogen increases the efficiency of chlorophyll [ 50 ]. In Bangladesh, from 2013 to 2014, a study assessed the impact of varying nitrogen doses on cabbage growth and yield, suggesting that utilizing 200 kg N/ha could be beneficial for cabbage cultivation [ 51 ]. If a plant is supplied with an optimum amount of nitrogen, there is a tendency to increase leaf cell number and cell size, with an overall increase in leaf production.…”
Section: The Effect Of Nitrogen On the Cabbage Yieldmentioning
confidence: 99%